Cytological technique as an adjunct to the teaching of sexual dimorphism in secondary school biology - Olaguer, Aurora P. 1945- (s.n.], 1969)
The aim of the study is to introduce simple techniques in demonstrating the phenomenon of sexual dimorphism at the micro level which high school students can use for cytological studies in differentiating sexual dimorphism at the cellular level.